Achieving huge extra improvements in thermal conductivity of carbon/polymer composites by pre-centrifugation. (October 2022) - Yuan, Tao; Zhang, Songdi; Liu, Jianping; Chen, Nipeng; Bao, Chenlu
Abstract: Huge extra improvements in thermal conductivity of carbon/polymer composites can be achieved by pre-centrifugation method. It is found that, based on the already improved thermal conductivity of carbon/polymer composites due to the incorporation of carbon fillers, thermal conductivity can be further increased when a pre-centrifugation treatment applies to raw material mixtures. When mass fraction of worm graphite is 25%, a simple pre-centrifugation treatment can improve the thermal conductivity of worm graphite/silicone rubber composites from 3.3 ± 0.1 W/mK to 14.4 ± 0.1 W/mK (4262% extra improvements), worm graphite/epoxy composites from 1.3 ± 0.1 W/mK to 10.2 ± 0.6 W/mK (3093% extra improvements), worm graphite/polyethylene glycol composites from 5.8 ± 0.1 W/mK to 17.4 ± 0.2 W/mK (6079% extra improvements), and worm graphite/poly(vinyl alcohol) composites from 0.6 ± 0.1 W/mK to 2.1 ± 0.1 W/mK (840% extra improvements), respectively. These huge improvements are mainly attributed to the overpacking effect of pre-centrifugation method. Besides, high and quasi-isotropic thermal conductivity can be obtained when centrifugal speed is lower than 14000 rpm. Graphical abstract: Image 1 Highlights: Extra thermal conductivity improvements have been obtained in carbon/polymer system. A pre-centrifugation strategy has been developed to improve the thermal conductivity. High and isotropic thermal conductivity (8–11.8 W/mK) has been achieved. Pre-centrifugation treatment can effectively compact the microstructure of composites.